The Effect of Knowledge of "Nutritional Action Materials" and Physical Activity as Efforts to Improve Nutrition on Adolescents in the Working Area of the Sekongkang Public health center - sholihah, Nur Arifatus (STRADA : Jurnal Ilmiah Kesehatan, 2024)
Adolescence is a transitional period in life when a person prepares himself to enter adulthood. During this period, teenagers experience changes in behavior from children to adults. Responding to these changes, teenagers experience physiological and psychological changes. Riskesdas data for 2010 shows that the percentage of irregular menstrual disorders in Indonesia was 13.7%. This study aims to determine how knowledge of balanced nutrition and physical activity influence the menstrual cycle in adolescents in the UPTD area of ​​the Sekongkang Community Health Center. The research is a cross-sectional type of analytical observational quantitative research. The sample size used in this research was 70 samples by taking samples using a cluster random sampling technique. Collecting data on knowledge of balanced nutrition, menstrual cycles using questionnaires and physical activity using the International Physical Activity Questinnaire (IPAQ).